Cytotoxic properties of a new organometallic platinum(ii) complex and its gold(i) heterobimetallic derivatives. Issue 2 (26th November 2015) - Serratrice, Maria; Maiore, Laura; Zucca, Antonio; Stoccoro, Sergio; Landini, Ida; Mini, Enrico; Massai, Lara; Ferraro, Giarita; Merlino, Antonello; Messori, Luigi; Cinellu, Maria Agostina
Abstract : The high antiproliferative effects of a new organoplatinum(ii ) complex are further enhanced upon coordination of a gold(i ) phosphane moiety. Abstract : A novel platinum(ii ) organometallic complex, [Pt(pbi)(Me)(DMSO)], bearing the 2-(2′-pyridyl)-benzimidazole (pbiH) ligand, was synthesized and fully characterized. Interestingly, the reaction of this organometallic platinum(ii ) complex with two distinct gold(i ) phosphane compounds afforded the corresponding heterobimetallic derivatives with the pbi ligand bridging the two metal centers. The antiproliferative properties in vitro of [Pt(pbi)(Me)(DMSO)] and its gold(i ) derivatives as well as those of the known coordination platinum(ii ) and palladium(ii ) complexes with the same ligand, of the general formula [MCl2 (pbiH)], were comparatively evaluated against A2780 cancer cells, either sensitive or resistant to cisplatin. A superior biological activity of the organometallic compound clearly emerged compared to the corresponding platinum(ii ) complex; the antiproliferative effects are further enhanced upon attaching the gold(i ) triphenylphosphine moiety to the organometallic Pt compound. Remarkably, these novel metal species are able to overcome nearly complete resistance to cisplatin. Significant mechanistic insight into the study compounds was gained after investigating their reactions with a few representative biomolecules by electrospray mass spectrometry and X-ray crystallography. The obtained results are comprehensively discussed.